A cytoarchitecture-driven myelin model reveals area-specific signatures in human primary and secondary areas using ultra-high resolution in-vivo brain MRI - Dinse, J.; Härtwich, N.; Waehnert, M.D.; Tardif, C.L.; Schäfer, A.; Geyer, S.; Preim, B.; Turner, R.; Bazin, P.-L. (NeuroImage (Orlando, Fla.), 2015)
This work presents a novel approach for modelling laminar myelin patterns in the human cortex in brain MR images on the basis of known cytoarchitecture. For the first time, it is possible to estimate intracortical contrast visible in quantitative ultra-high resolution MR images in specific primary and secondary cytoarchitectonic areas. The presented technique reveals different area-specific signatures which may help to study the spatial distribution of cortical T1 values and the distribution of cortical myelin in general. It may lead to a new discussion on the concordance of cyto- and myeloarchitectonic boundaries, given the absence of such concordance atlases. The modelled myelin patterns are quantitatively compared with data from human ultra-high resolution in-vivo 7T brain MR images (9 subjects). In the validation, the results are compared to one post-mortem brain sample and its ex-vivo MRI and histological data. Details of the analysis pipeline are provided. In the context of the increasing interest in advanced methods in brain segmentation and cortical architectural studies, the presented model helps to bridge the gap between the microanatomy revealed by classical histology and the macroanatomy visible in MRI. •We present a model that predicts T1 contrast related to myelin as measured with MRI.•The predictions are based on cytoarchitectural a-priori information.•When compared to in-vivo T1 maps the model reveals area-specific signatures.•Quantitative analysis shows agreement between in-vivo T1 maps and model.•Visual comparison to classical histology data is provided.